De novo SCN1A mutations in Dravet syndrome and related epileptic encephalopathies are largely of paternal origin. Issue 2 (8th July 2009) - Heron, Sarah E; Scheffer, Ingrid E; Iona, Xenia; Zuberi, Sameer M; Birch, Rachael; McMahon, Jacinta M; Bruce, Carla M; Berkovic, Samuel F; Mulley, John C
Abstract : Background: Dravet syndrome is a severe infantile epileptic encephalopathy caused in approximately 80% of cases by mutations in the voltage gated sodium channel subunit gene SCN1A . The majority of these mutations are de novo. The parental origin of de novo mutations varies widely among genetic disorders and the aim of this study was to determine this for Dravet syndrome. Methods: 91 patients with de novo SCN1A mutations and their parents were genotyped for single nucleotide polymorphisms (SNPs) in the region surrounding their mutation. Allele specific polymerase chain reaction (PCR) based on informative SNPs was used to separately amplify and sequence the paternal and maternal alleles to determine in which parental chromosome the mutation arose. Results: The parental origin of SCN1A mutations was established in 44 patients for whom both parents were available and SNPs were informative. The mutations were of paternal origin in 33 cases and of maternal origin in the remaining 11 cases. De novo mutation of SCN1A most commonly, but not exclusively, originates from the paternal chromosome. The average age of parents originating mutations did not differ from that of the general population. Conclusions: The greater frequency of paternally derived mutations in SCN1A is likely to be due to the greater chance of mutational events during the increased number of mitoses which occur during spermatogenesis compared to oogenesis, and the greater susceptibility to mutagenesis of the methylated DNA characteristic of sperm cells.